ANALYSIS OF STUDENTS' MATHEMATIC COMMUNICATION ABILITY IN SOLVING MATHEMATICS PROBLEMS AT SENIOR HIGH SCHOOL - Eryna Pudi Kania; Nailul Authary; Novi Trina Sari (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2021)
The ability of students in learning Mathematics Senior high school, still cannot be categorized as good, because students who have only been able to work on questions without being able to communicate it well back to other parties. This study raises the problem of how students' mathematical communication skills in solving mathematics problems at Senior high school?. This study aims to determine students' mathematical communication skills in solving mathematical problems at Senior high school. This research uses field research method with qualitative approach and descriptive research type. The subjects of this study consisted of three students. Data collection techniques were carried out by tests and interviews. The data was then analyzed using a qualitative descriptive approach. Based on the results of the study, it can be seen that the mathematical abilities of the students of Senior high school Sabang City can be classified into three levels of ability, namely students with high, medium and low abilities. Students who have high abilities in addition to being able to work on questions well are also able to communicate them to others. Students who have moderate mathematical ability are only able to do one aspect, namely only being able to work on questions without being able to communicate them well to other parties. Meanwhile, low-ability students are only able to solve problems and are not good at communicating mathematically to other parties.